Boundary-Value Problem for Linear Parabolic Equations with Degeneracies - Pukalskyi, I. D. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
In spaces of classical functions with power weight, we prove the correct solvability of a boundary-value problem for parabolic equations with an arbitrary power order of degeneracy of coefficients with respect to both time and space variables.